Hypocomplementemia dynamics during tocilizumab therapy in systemic juvenile idiopathic arthritis: a retrospective longitudinal study - Ling, Jiayun; Zhou, Qingfang; Xie, Fang; Liu, Xiaohui (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to investigate the trajectory of complement C3 and C4 levels during tocilizumab (TCZ) treatment in patients with systemic juvenile idiopathic arthritis (sJIA), explore the dynamic relationship between hypocomplementemia and disease activity, and characterize adverse events during long-term TCZ therapy.MethodsA retrospective analysis was conducted on 19 sJIA patients diagnosed according to the 2019 PRINTO criteria. Clinical data, including C3 and C4 levels, disease activity (sJADAS10-ESR score), and adverse events, were collected at baseline and at intervals from 2 to 96 weeks following TCZ initiation. Statistical analyses were conducted accordingly.ResultsThe 19 analyzed patients (6 males, 31.58%; 13 females, 68.42%) had a median (IQR) age of disease onset of 6.75 (4.58-9.42) years and a median (IQR) follow-up duration of 2.08 (1.83-2.67) years. After 2 weeks of TCZ treatment, median (IQR) serum C3 levels declined from 1.45(1.27-1.75) g/L at baseline to 1.11 (0.97-1.18) g/L (a 23.45% reduction, P = 0.009), and C4 levels decreased from 0.29 (0.21-0.38) g/L to 0.13 (0.09-0.17) g/L (a 55.17% reduction, P = 0.005). At week 48, hypocomplementemia was observed in 68.42% of patients for C3 and 26.32% for C4. The mixed linear model revealed significant reductions in C3 (β = -0.058, P < 0.001), C4 (β = -0.061, P = 0.022), and sJADAS10-ESR scores (β = -0.628, P < 0.001) across all time points compared to baseline. Longitudinal Spearman analysis revealed a positive correlation between complement levels and disease activity at specific stages: C3 (r = 0.529, P = 0.029) and C4 (r = 0.577, P = 0.015) were most strongly correlated with sJADAS10-ESR at week 24. Notably, C3 remained significantly correlated at week 48 (r = 0.513, P = 0.025). Acute upper respiratory tract infections were the most common adverse events (occurring in 63.16% of patients), while no serious infections or new autoimmune diseases were reported.ConclusionsComplement C3 and C4 levels during TCZ treatment follow a trajectory characterized by a rapid early decline followed by a sustained low-level plateau. Long-term hypocomplementemia appears to be well tolerated, with no increased risk of serious infections or autoimmune complications. These findings suggest that hypocomplementemia reflects deep IL-6 signaling inhibition rather than pathological complement consumption.